Covid and social work in Spain and Italy: From initial uncertainty to operational transformation of services - Fernández Borrero, Manuela A.; di Pietro, Cristiana; Sibilla, Marinella; Cimagalli, Folco (Cuadernos de Trabajo Social, 2025)
During the pandemic, social services underwent profound transformations, which directly affected both social workers and directly affects both social workers and clients. and the people who use them. They had to adapt quickly, incorporating preventive preventive measures, and adjusting working procedures. This article presents the main results of quantitative research carried out in Spain and replicated in Italy during the Spain, and replicated in Italy during the pandemic. In the survey, conducted between July and October of that year in Italy, involving 214 civil servants in the social services sector. officials working in the public and private social services sectors and 560 in Spain in the and 560 in Spain in April 2020, respectively. The results show the relevance of the factors that make professionals value the measures adopted both in their services and work. adopted both in their services and in their centers. It also takes into account. Those directly related to the vulnerable population were also considered. Vulnerable population. The perception of the measures was analyzed, as well as the methodological modifications in the action after the introduction of the measures. methodological modifications in action after the introduction of the changes. changes. The effect on the general public is also considered. All this, given that social services, as a result of this exceptional situation, have undergone and are undergoing relevant changes in their functioning, have undergone and are undergoing significant changes in their functioning and in their responses to the dynamics and and their responses to the dynamics and situations they deal with.